2012
DOI: 10.1016/j.biopsych.2011.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Val66Met Allele Impairs Basal and Ketamine-Stimulated Synaptogenesis in Prefrontal Cortex

Abstract: Background Knock-in mice with the common human BDNF Val66Met polymorphism have impaired trafficking of BDNF mRNA to dendrites. Given evidence that local synapse formation is dependent on dendritic translation of BDNF mRNA, it was hypothesized that loss-of-function Met allele mice would show synaptic deficits both at baseline and in response to ketamine, an NMDA antagonist that stimulates synaptogenesis in prefrontal cortex (PFC). Methods Whole-cell recordings from layer V medial PFC pyramidal cells in brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
308
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 356 publications
(329 citation statements)
references
References 58 publications
(81 reference statements)
16
308
2
3
Order By: Relevance
“…Ketamine increases glutamate transmission in the prefrontal cortex, presumably by eliciting a disinhibition of GABAergic input that results in an enhancement of the firing rate of glutamatergic neurons thought to underlie ketamine induction of synaptogenesis (Li et al, 2010(Li et al, , 2011. Interestingly, the antidepressant effect of ketamine is attenuated in both animals and humans with the Met allele of the BDNF gene (Laje et al, 2012;Liu et al, 2012), an observation that may render BDNF genotyping an important biomarker for the clinical response to ketamine in humans. However, in our study, we did not observe a significant effect of the BDNF polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine increases glutamate transmission in the prefrontal cortex, presumably by eliciting a disinhibition of GABAergic input that results in an enhancement of the firing rate of glutamatergic neurons thought to underlie ketamine induction of synaptogenesis (Li et al, 2010(Li et al, , 2011. Interestingly, the antidepressant effect of ketamine is attenuated in both animals and humans with the Met allele of the BDNF gene (Laje et al, 2012;Liu et al, 2012), an observation that may render BDNF genotyping an important biomarker for the clinical response to ketamine in humans. However, in our study, we did not observe a significant effect of the BDNF polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Both processing speed and attention have been linked to dopamine functioning within prefrontal-subcortical circuits (Cropley et al, 2006), and ketamine is known to modulate dopamine signaling within the striatum and prefrontal cortex in animals (Moghaddam et al, 1997) and humans (Kegeles et al, 2000;Rabiner, 2007;Smith et al, 1998). Mechanistic studies in animals show that ketamine rapidly enhances synaptic plasticity at the level of prefrontal cortical neurons (Li et al, 2010(Li et al, , 2011, and is able to rapidly reverse stress-induced dendritic atrophy and behavioral depression in a brain-derived neurotrophic factor (BDNF)-dependent manner (Li et al, 2011;Liu et al, 2012). A recent study found that ketamine reversed deficit dopamine signaling in a learned helplessness model of depression and normalized synaptic plasticity within the nucleus accumbens (indexed by long-term potentiation) via activation of dopamine D1 receptors (Belujon and Grace, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this polymorphism interacts with antidepressant efficacy because Met carriers appear to exhibit a better response to classical antidepressants (Choi et al, 2006;Niitsu et al, 2013). Nevertheless, such observations are highly dependent on the type of antidepressant, gender, ethnicity and the presence of other polymorphisms (Brunoni et al, 2013;Liu et al, 2012;Tsai et al, 2010;Wang et al, 2014), suggesting only a weak association between rs6265 and antidepressant response.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this polymorphism interacts with antidepressant efficacy because Met carriers appear to exhibit a better response to classical antidepressants (Choi et al, 2006;Niitsu et al, 2013). Nevertheless, such observations are highly dependent on the type of antidepressant, gender, ethnicity and the presence of other polymorphisms (Brunoni et al, 2013;Liu et al, 2012;Tsai et al, 2010;Wang et al, 2014), suggesting only a weak association between rs6265 and antidepressant response.BDNF is a critical pro-survival factor for the developing and adult central nervous system, through modulation of activity-induced neuronal plasticity (Park and Poo, 2013), and has been repeatedly implicated in the etiology of depression. Moreover, its antidepressant properties are now clearly demonstrated and led to Epigenetic mechanisms underlying the role of brain-derived neurotrophic factor in depression and response to antidepressants…”
mentioning
confidence: 99%